2007
DOI: 10.1099/mic.0.2007/011049-0
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus neoformans laccase catalyses melanin synthesis from both d- and l-DOPA

Abstract: The human fungal pathogen Cryptococcus neoformans produces melanin in the presence of various substrates, including the L enantiomer of 3,4-dihydroxyphenylalanine (DOPA). The enzyme laccase catalyses the formation of melanin by oxidizing L-DOPA, initiating a series of presumably spontaneous reactions that ultimately leads to the polymerization of the pigment in the yeast cell wall. There, melanin protects the cell from a multitude of environmental and host assaults. Thus, the ability of C. neoformans to produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(81 citation statements)
references
References 40 publications
3
73
0
2
Order By: Relevance
“…D-DOPA can also serve as a substrate, and melanization occurred equally well with both enantiomers (15). Both laccase and the pigment melanin are associated with the virulence of C. neoformans (39,40,47,58).…”
Section: Discussionmentioning
confidence: 99%
“…D-DOPA can also serve as a substrate, and melanization occurred equally well with both enantiomers (15). Both laccase and the pigment melanin are associated with the virulence of C. neoformans (39,40,47,58).…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of 3,4-dihydroxy-L-phenylalanine (L-DOPA), a PPO substrate that is also oxidized by laccases (Eisenman et al, 2007) and peroxidases (Albrecht and Kohlenbach, 1990), we observed total latex enzymatic activities of approximately 0.218 mkat mg 21 (T. officinale) and approximately 0.237 mkat mg 21 (T. kok-saghyz). Addition of the potent PPO inhibitor tropolone (Fuerst et al, 2006) caused a significant reduction in the total enzymatic activity to approximately 0.004 mkat mg 21 for T. officinale and approximately 0.002 mkat mg 21 for T. koksaghyz (Fig.…”
Section: Identification and Molecular Characterization Of Enzymes Invmentioning
confidence: 99%
“…This basidiomycetous fungus infects the human brain and it contains a very active phenol oxidase able to oxidize the catecholamine neurotransmitters, dopamine, and norepinephrine to melanin polymers [120,121]. As these pigments are formed in the brain after infection, a pathogenic neuromelanin is formed using brain compounds [122] and that increases the virulence of the infection. On the other hand, C. neoformans is also able to synthesize pyomelanin derived from a fungal metabolite, homogentisic acid (HGA, Figure 1(h)) [123].…”
Section: New Journal Of Sciencementioning
confidence: 99%